Tourism Development in Goa: Trends, Importance and Challenges - Achrekar, Geetanjali (International Journal of Multidisciplinary in Management and Tourism, 2020)
The paper focuses on the growth of tourism in Goa since it became free as a Portuguese colony i.e. 1961 till 2014. Contribution of tourism sector to the growth of the state economy, in terms of income, employment, foreign exchange earnings and linkages with other sectors has been growing. Though Goa’s economy is driven by tourism sector today, the rapid growth of domestic tourism and foreign tourism in the state has posed various environment problems and challenges which are faced by the stakeholders and state. Relevant policy recommendations are suggested for the balanced growth of this vital sector of Goa's economy.